Implementation of Intercultural Dialogue at Saverius Gunungsitoli Nias High School - Dominikus Doni Ola*; Renata Dewi Yulianti Waruwu; Antonius P Sipahutar (Riwayat: Educational Journal of History and Humanities, 2023)
Cultural pluralism at Saverius Gunungsitoli Nias High School triggers conflict among students when the learning process ignores the implementation of cultural values held by students in the curriculum. This study aims to explore the idea of implementing intercultural dialogue into the learning curriculum at SMA Saverius Gunungsitoli Nias. The aim is to educate and guide students to be able to accept, appreciate, and respect others with different cultural backgrounds. Library research (library research), which is supported by existing reference sources, such as documents, books, journals, magazines, and other print media related to the research theme was chosen as the method. This research found that educators in Catholic school foundations had not yet implemented an integrated curriculum with the theme of intercultural dialogue. The basic spirit of Catholic schools, namely brotherly love among fellow human beings and the characteristics of Catholic schools as a place for dialogue and peaceful encounters to encourage an attitude of recognizing and respecting differences, is expected to be truly implemented through its curriculum. The goal is that students are able to make friends and work together with people of different cultural backgrounds. This research can add to the body of knowledge in the field of education and intercultural dialogue, including interreligious dialogue.